Primary ovarian carcinoid: a case report - Kaur, Jameen; Goel, Bharti; Sehgal, Alka; Jaswal, Vidhu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Primary ovarian carcinoid tumor is a rare entity, usually seen in perimenopausal or menopausal age group, it’s rarely malignant. A case study of a 53yr old female who presented with a large primary ovarian carcinoid is being reported here.